2020
DOI: 10.3389/fcell.2020.601043
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Promotes Trophoblast Cell Induced Separation of Vascular Smooth Muscle Cells in Vascular Remodeling via Induction of G-CSF

Abstract: Vitamin D deficiency is associated with complications of pregnancy such as pre-eclampsia, fetal growth restriction, and miscarriage, all of which are also associated with incomplete spiral artery (SpA) remodeling. We have previously shown that both uterine natural killer (uNK) cells and extravillous trophoblast cells (EVT) are required for successful SpA remodeling, but whether their activity in this process is modulated by vitamin D is not known. In the current study, we use a previously described chorionic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…The plausibility of a role for vitamin D in pregnancy and miscarriage is supported by the expression of the vitamin D-activating enzyme CYP27B1 in maternal decidua and fetal trophoblast early in pregnancy (14). In previous studies, we have shown that the human placenta is a key tissue for the accumulation of both 25(OH)D and active 1,25-dihydroxyvitamin D (1,25(OH) 2 D) (15), with the potential to exert important effects on trophoblast invasion, placental spiral artery remodeling, and immune cell function (16)(17)(18). These processes are impaired in human miscarriage, with aberrant endometrial receptivity and dysregulated placentation identified early after initial conception (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The plausibility of a role for vitamin D in pregnancy and miscarriage is supported by the expression of the vitamin D-activating enzyme CYP27B1 in maternal decidua and fetal trophoblast early in pregnancy (14). In previous studies, we have shown that the human placenta is a key tissue for the accumulation of both 25(OH)D and active 1,25-dihydroxyvitamin D (1,25(OH) 2 D) (15), with the potential to exert important effects on trophoblast invasion, placental spiral artery remodeling, and immune cell function (16)(17)(18). These processes are impaired in human miscarriage, with aberrant endometrial receptivity and dysregulated placentation identified early after initial conception (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…3a–c), which suggested that VD 3 -induced granulopoiesis was independent on the microbiota in the early developmental stage of zebrafish. Interestingly, a recent report demonstrated that VD promoted G-CSF production in placental explants [42] Considering the fact that the whole gastrointestinal tube opens in the zebrafish at 6 dpf, and commensal bacteria colonize the intestine of zebrafish over the course of several weeks [43, 44], we suggest that VD/VDR signaling might directly regulate neutrophil granulopoiesis and the gene expression of csf3 in the early development as a transcription factor.…”
Section: Discussionmentioning
confidence: 85%
“…Slides were cooled and washed prior to blocking in 5X Casein (Thermo Scientific) for 30 min at room temperature. Sections were then incubated overnight with primary antibody, rabbit anti‐G‐CSF (Abcam) 31 . Sections were washed, and secondary antibody (Universal ImmPRESS antibody, Vector Laboratories, Burlingame, USA) was added at room temperature for 30 min, followed by further washing and addition of DAB substrate (ImmPACT DAB, Vector Laboratories) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Sections were then incubated overnight with primary antibody, rabbit anti-G-CSF (Abcam). 31 Sections were washed, and secondary antibody (Universal ImmPRESS antibody, Vector Laboratories, Burlingame, USA) was added at room temperature for 30 min, followed by further washing and addition of DAB substrate (ImmPACT DAB, Vector Laboratories) for 5 min. After counterstaining with Harris's haematoxylin (Sigma-Aldrich), slides were dehydrated using ethanol and Histoclear and mounted using OmniMount (National Diagnostics).…”
Section: Rna Extraction and Rt-qpcrmentioning
confidence: 99%